2021
DOI: 10.3390/ijerph181910127
|View full text |Cite
|
Sign up to set email alerts
|

From a Symptom-Based to a Person-Centered Approach in Treating Depressive Disorders in Adolescence: A Clinical Case Formulation Using the Psychodynamic Diagnostic Manual (PDM-2)’s Framework

Abstract: Background: Depressive disorders in adolescence are among the most challenging clinical syndromes to diagnostically identify and treat in psychotherapy. The Psychodynamic Diagnostic Manual, Second Edition (PDM-2) proposes an integration between nomothetic knowledge and an idiographic understanding of adolescent patients suffering from depression to promote a person-centered approach. This single-case study was aimed at describing and discussing the clinical value of an accurate diagnostic assessment within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Moreover, the findings suggest that the PDC-C can generate clinically meaningful diagnoses to inform individualized clinical interventions tailored to children’s core psychological features. Thus, in line with the literature (Bornstein & Gordon, 2012; Gordon & Bornstein, 2018 ; Tanzilli et al ., 2021b ), the present results provide empirical support for the clinical utility of the PDC-C as a valid assessment of psycho(patho)logical constructs.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, the findings suggest that the PDC-C can generate clinically meaningful diagnoses to inform individualized clinical interventions tailored to children’s core psychological features. Thus, in line with the literature (Bornstein & Gordon, 2012; Gordon & Bornstein, 2018 ; Tanzilli et al ., 2021b ), the present results provide empirical support for the clinical utility of the PDC-C as a valid assessment of psycho(patho)logical constructs.…”
Section: Discussionsupporting
confidence: 67%
“…Studies on the Psychodiagnostic Chart for adults (PDC - 2; Gordon & Bornstein, 2015 ) and adolescents (PDC-A; Malberg, Malone, Rossberg, & Speranza, 2017) have shown it to be a valid and reliable instrument for initial diagnoses, identifying treatment targets and tracking progress throughout and after treatment; they have also shown it to be applicable to various teaching and research contexts (see, Brabender & Whitehead, 2011 ; Gordon & Bornstein, 2018 ; Gordon et al ., 2013 ; Spektor et al ., 2015 ; Tanzilli et al ., 2021b ). However, to the best of our knowledge, no research has empirically explored the psychometric properties of the PDC - C and its use in child clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, because only the global score was included in our network, our findings cannot identify which specific structural functions are most relevant in patients with depression or somatization. However, for clinical case formulations a more detailed understanding of the various aspects of personality functioning is required (Tanzilli et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the common ego-syntonic and reinforcing nature of several ED symptoms, as well as patients' lack of insight or even denial of the illness, may limit the ability of self-report measures to detect changes in symptoms throughout treatment. The PDC-2 has been used extensively to evaluate patients' treatment progress in single case studies, revealing its validity and utility as an effective tool to explore both symptom changes and "structural" changes in personality organization over time, according to patient narratives [64,65].…”
Section: Is the Pdm-2 Approach Supported By Empirical Research?mentioning
confidence: 99%
“…Both single cases and quantitative studies involving different clinical populations have shown that the PDC-2 supports the assessment of key dimensions of psychological functioning underlying observable symptoms, including defense mechanisms, mental functioning capacities, and personality styles or types [39,55,[64][65][66]. For instance, the single case study by Tanzilli et al [65] employed the PDC-2 to obtain a comprehensive picture of an adolescent patient with major depressive disorder through the lens of mental functioning and levels of personality organization. Specifically, a borderline personality organization was found to be associated with an impaired ability to engage in stable and satisfying intimate relationships and to regulate selfesteem, which, in turn, impacted on the psychodynamic psychotherapy outcome.…”
Section: Is the Pdm-2 Approach Supported By Empirical Research?mentioning
confidence: 99%